Folkloristics, Cultural Studies and Popular Culture - Narváez, Peter (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
Folklorists have examined four relations of folklore and contemporary popular culture: the incorporation of folklore into popular art; traditions engendered within the discourses and production of popular culture; the expressive uses of mass culture in small group contexts; and, popular folk revivals. Students of “cultural studies,” an international academie development which began at the University of Birmingham in the 1960s, have made significant contributions to the study of popular culture, and these works exhibit interests that are akin to those of folklorists. Fundamentally, both fields entertain a humanistic, holistic, nonhierarchical view of “culture”. Moreover, what cultural studies deems as “popular culture,” folklorists anayze as the expressive uses of mass culture in small group contexts, that is, modem folklore. The pluralistic and functional social assumptions of folklorists, however, are at odds with cultural studies’ understanding of society as a complex set of power relations in dynamic flux. Especially relevant to cultural studies in this regard is Antonio Gramsci’s theory of hegemony. This frame is particularly useful to the contextual study of forms of folklore and popular culture that pose an antithetical edge. In turn, cultural studies might benefit from an ethnographic appreciation of the role of cultural continuity and tradition, a method well cultivated in folkloristics.